Floristic range ridge dendroflor Ugam (Experimental biology, 2016)
Ridge dendroflor Ugam – one of large components of the Western Tien Shan are presented in article a floristic range. The range is made on classification of the academician A. L. Takhtadzhyan. It is as a result revealed specific structure dendroflor – 120 types relating to 51 childbirth from 24 semeystvampreobladayushchy number of types of an otnesn\ena to Rosaceae, Lamiaceae, Fabaceae, Salicaceae, Caprifoliaceae, Asteraceae, Ranunculaceae, Tamaricaceae and Rhamnaceae families.
Keywords: Floristic range; the Western Tien Shan; Ugamsky ridge; dendroflor; family; taxons; sort; look.